EKSPLOITASI ANAK JALANAN SEBAGAI PENGEMIS DI KAWASAN SIMPANG LIMA SEMARANG - Rochatun, Isti (Civic Education Program, Universitas Negeri Semarang, 2015)
The phenomenon of street children in Indonesia spread is a complex social problems .. Problems in this study were (1) why there is exploitation of street children as beggars in the Simpang Lima Semarang, (2) What forms of exploitation of street children in Semarang Simpang Lima area, and (3) What is the impact of child abuse against street children and the community in the Simpang Lima Semarang. This study uses qualitative research methods. The data was collected using observation techniques, interviews, and documentation. The results showed that there are three things that the background for the exploitation of street children Simpang Lima area of Semarang d namely: low family economic (poverty), community and environmental influences and the cracks and violent home life parents. Forms of exploitation of street children in Semarang Simpang Lima area is conducted by parents and are carried out by thugs. Impact of exploitation of children can include miraculous things: economics, health, psychological and educational for people while the impact of exploitation include: making restless road users, mengaggu traffic order and make people uneasy.